Disopyramide use in infants and children with hypertrophic cardiomyopathy. (7th March 2018) - O'Connor, Matthew J.; Miller, Kelley; Shaddy, Robert E.; Lin, Kimberly Y.; Hanna, Brian D.; Ravishankar, Chitra; Rossano, Joseph W.
Abstract: Hypertrophic cardiomyopathy has a range of clinical severity in children. Treatment options are limited, mainly on account of small patient size. Disopyramide is a sodium channel blocker with negative inotropic properties that effectively reduces left ventricular outflow tract gradients in adults with hypertrophic cardiomyopathy, but its efficacy in children is uncertain. A retrospective chart review of patients ⩽21 years of age with hypertrophic cardiomyopathy at our institution and treated with disopyramide was performed. Left ventricular outflow tract Doppler gradients before and after disopyramide initiation were compared as the primary outcome measure. Nine patients received disopyramide, with a median age of 5.6 years (range 6 days–12.9 years). The median left ventricular outflow tract Doppler gradient before initiation of disopyramide was 81 mmHg (range 30–132 mmHg); eight patients had post-initiation echocardiograms, in which the median lowest recorded Doppler gradient was 43 mmHg (range 15–100 mmHg), for a median % reduction of 58.2% (p=0.002). With median follow-up of 2.5 years, eight of nine patients were still alive, although disopyramide had been discontinued in six of the nine patients. Reasons for discontinuation included septal myomectomy (four patients), heart transplantation (one patient), and side effects (one patient). Disopyramide was effective for the relief of left ventricular outflow tract obstruction in children with hypertrophic cardiomyopathy, although longer-term data suggest that its efficacy is not sustained. In general, it was well tolerated. Further study in larger patient populations is warranted.